Cultural Terms in Gospel of Mark : a Translation Study - juan, fidelio; Lagung, Sirilus; Sukarsih, Ni Nyoman Tri (LPPM Universitas Dhyana Pura, 2023)
Translation procedures involve complex processes of linguistic and cultural analysis by examining the text through systematic methods aimed at preserving meaning and readability. This study investigates the application of Newmark's translation procedures, with a focus on cultural terms and cultural equivalence, in the translation of the Gospel of Mark from English to Indonesian. Utilizing Newmark's framework, which includes methods such as transference, Naturalization, cultural equivalent, and functional equivalent among others, the study employs a qualitative descriptive analysis method. Data was collected through non-participant observation and non-probability sampling on selected cultural terms from the Gospel of Mark. The findings reveal that while cultural equivalence is crucial for conveying the original cultural context, other procedures are necessary to address different linguistic and contextual challenges. Newmark's procedures facilitate a nuanced translation process, ensuring that the cultural context and original meaning of the terms are preserved while making them accessible to contemporary Indonesian readers. The study demonstrates that a balanced application of Newmark's translation procedures results in a more faithful and culturally appropriate translation of religious texts.